Simulation of Performance of Earth-Tube Heat Exchanger Using A Mathematical Model - Sharan, Girija; Madhavan, T (Journal of Agricultural Engineering, 2003)
A mathematical model of single-pass earth-tube heat exchanger (ETHE) is presented. Solution of heat transfer equation is obtained using finite element method. Finite element method uses Galerkin formulation and triangular elements in cylindrical coordinates. ETHE consists of a single pipe buried 3-m deep. Air at a known constant temperature is pumped through the pipe. Solutions yield air temperature down the length of pipe and soil temperature around the pipe. Cooling mode solutions are compared with empirical measurements and found satisfactorily close. Computations using the model as well as actual measurements show that ETHE could be operated in cooling mode for at least eight hours continuously without noticeable degradation in performance.